Monitoring and parenteral administration of micronutrients, phosphate and magnesium in critically ill patients: The VITA-TRACE survey. Issue 2 (February 2021) - Vankrunkelsven, Wouter; Gunst, Jan; Amrein, Karin; Bear, Danielle E.; Berger, Mette M.; Christopher, Kenneth B.; Fuhrmann, Valentin; Hiesmayr, Michael; Ichai, Carole; Jakob, Stephan M.; Lasocki, Sigismond; Montejo, Juan C.; et al.
Summary: Background & aims: Despite the presumed importance of preventing and treating micronutrient and mineral deficiencies, it is still not clear how to optimize measurement and administration in critically ill patients. In order to design future comparative trials aimed at optimizing micronutrient and mineral management, an important first step is to gain insight in the current practice of micronutrient, phosphate and magnesium monitoring and administration. Methods: Within the metabolism-endocrinology-nutrition (MEN) section of the European Society of Intensive Care Medicine (ESICM), the micronutrient working group designed a survey addressing current practice in parenteral micronutrient and mineral administration and monitoring. Invitations were sent by the ESICM research department to all ESICM members and past members. Results: Three hundred thirty-four respondents completed the survey, predominantly consisting of physicians (321 [96.1%]) and participants working in Europe (262 [78.4%]). Eighty-one (24.3%) respondents reported to monitor micronutrient deficiencies through clinical signs and/or laboratory abnormalities, and 148 (44.3%) reportedly measure blood micronutrient concentrations on a routine basis. Two hundred ninety-two (87.4%) participants provided specific data on parenteral micronutrient supplementation, of whom 150 (51.4%) reported early administration of combined multivitamin and trace element preparations at least in selected patients. Among specific parenteral micronutrient preparations, thiamine (146 [50.0%]) was reported to be the most frequently administered micronutrient, followed by vitamin B complex (104 [35.6%]) and folic acid (86 [29.5%]). One hundred twenty (35.9%) and 113 (33.8%) participants reported to perform daily measurements of phosphate and magnesium, respectively, whereas 173 (59.2%) and 185 (63.4%) reported to routinely supplement these minerals parenterally. Conclusion: The survey revealed a wide variation in current practices of micronutrient, phosphate and magnesium measurement and parenteral administration, suggesting a risk of insufficient prevention, diagnosis and treatment of deficiencies. These results provide the context for future comparative studies, and identify areas for knowledge translation and recommendations.